تحليل أثر السياسات الاقتصادية على ميزان المدفوعات في الدول النامية "دراسة قياسية للفترة 2000-2018" - منصوري, الحاج العربي (جامعة الوادي - University of Eloued, 2023)
The study attempts to analyze the impact of economic policies on the balance of payments during the period from (2000-2018) using cross-sectional data models (Panel Data Models). And Oceania, and they are among the countries classified in the lower bracket of middle-income countries according to the classification of the World Bank, and this was done by testing a standard model related to the coordination of economic policies and their impact resulting from the interaction and integration of policies in the balance of payments. Relationship, And that the balance of payments balance is positively affected by each of the following variables: the general government debt, the official exchange rate and the index of economic freedom, while it is negatively affected by each of the following variables: government spending, the tax burden index, and the real effective exchange rate had no effect on the balance of payments during the study period.
Analyzing the impact of economic policies on the balance of payments in developing countries "Standard Study for the Period 2000-2018"
مقال
Keywords: financial policy tools; monetary policy tools; trade policy tools; Balance of Payments; Developing countries; Panel Data Models